Using web-sourced photography to explore the diet of a declining African raptor, the Martial Eagle (Polemaetus bellicosus). (13th February 2019) - Naude, Vincent N; Smyth, Lucy K; Weideman, Eleanor A; Krochuk, Billi A; Amar, Arjun
ABSTRACT: Understanding a species' diet can be critical for effective conservation. While several traditional methods for assessing raptor diet exist, many pose inherit biases and often require extensive fieldwork that can limit sample sizes and the geographic scope of studies. This is especially true for species that nest at low densities (e.g., large eagles). Recently, several studies have demonstrated the value of web-sourced photographs in tackling ecological and evolutionary questions. Specialized software (e.g., MORPHIC) has been developed to systematically extract Google Images for this purpose. We used this approach to explore the diet of Martial Eagles ( Polemaetus bellicosus ). A shortage of prey is one of the proposed hypotheses for recent population declines across their range. Of the 4, 872 photographs selected by MORPHIC, 254 were usable (5%). Birds, mammals, and reptiles each contributed similarly to overall identified prey. Helmeted Guineafowl ( Numida meleagris ) were the most important bird prey identified (12% of overall prey). The 4 most important mammalian prey species were Thompson's gazelle ( Eudorcas thomsonii ; 5%), impala ( Aepyceros melampus ; 4%), common duiker ( Sylvicapra grimmia ; 4%), and banded mongoose ( Mungos mungo ; 4%). Reptile prey was dominated by monitor lizards ( Varanus spp.; 21%). Prey class proportions differed significantly by regions with mammalian prey being more common in eastern Africa and reptile prey being more common in southern Africa. Within South Africa, reptile prey proportion was greater in the east than in the west. These corroborate existing prey composition studies. Prey composition differed between age classes, with adult eagles preying on more birds than non-adults. There was no significant difference in the average estimated prey weight by eagle age or feeding position (ground, perched, or flying). Our results suggest that this approach may offer a useful method to explore the diet for raptor species that are well photographed across their range, at minimal cost and research effort.